Male Sex Pheromone of the Parasitoid Wasp Urolepis rufipes Demonstrates Biosynthetic Switch Between Fatty Acid and Isoprenoid Metabolism Within the Nasonia Group - Ruther, Joachim; Wittman, Tyler; Grimm, Christopher; Feichtner, Florian S.; Fleischmann, Sonja; Kiermaier, Josef; King, Bethia H.; Kremer, Werner; Kalbitzer, Hans Robert; Schulz, Stefan (Frontiers in Ecology and Evolution, 2019)
Sex pheromones play a crucial role in the mate finding process of insects. The information has to be encoded in a species specific manner to avoid fitness costs due tocourtship by or even mismating with closely related species. Hence, sex pheromones typically diversify when new species evolve. Pheromones of closely related species typically vary in their chemical composition, but the compounds they use are often biosynthetically related. The biosynthetic pathways of insect pheromones are variations of conserved pathways that lead to primary and secondary metabolites. A switch from one pathway to another, particularly in species that use the same type of pheromone glands, is the exception. Here we use chemical analyses and behavioral bioassays to examine the male sex pheromone of the parasitoid wasp Urolepis rufipes. The genus Urolepis is most closely related to Nasonia and Trichomalopsis, forming the so-called “Nasonia group”. All Nasonia species and T. sarcophagae, the only Trichomalopsis species studied so far, produce fatty acid-derived hydroxylactones in their rectal vesicle. The pheromones are deposited on the ground and other substrates and attract virgin females. We show that males of U. rufipes produce a sex pheromone in the same gland and use it in the same manner as the other species of the Nasonia group. Structure elucidation and stable isotope labelling experiments revealed, however, that the U. rufipes pheromone is 2,6-dimethyl-7-octene-1,6-diol, a monoterpenoid derived from the mevalonate pathway. This suggests a biosynthetic switch between the fatty acid and isoprenoid metabolism in the Nasonia group.